THE IMPACT OF CIVIC EDUCATION ON SOCIAL BEHAVIOR CHANGES AND CRITICAL THINKING SKILLS OF GEN Z AT BANYUWANGI STATE POLYTECHNIC - Ninik Sri Rahayu Wilujeng (CV. RADJA PUBLIKA, 2025)
Civics education is a key factor in shaping the social and critical behavior of the younger generation in the digital era. It is known that Gen Z's social behavior lately when giving criticism on social media can be said to be impolite. In addition, they are also less concerned about the environment. This study aims to analyze the impact of civics education on the social behavior and critical thinking of Gen Z (students) at Banyuwangi State Polytechnic. This research method uses a quantitative approach with a survey method of 150 students, data collected through a Likert-scale-based questionnaire that measures aspects of social concern, public participation, and critical thinking. The results show a significant positive correlation between the level of understanding of civics education on social behavior and critical thinking skills of students (Gen Z). The highest correlation coefficient is found in the relationship between understanding of Civics Education and Critical Thinking Skills with r = 0.921 (p < 0.01). This finding confirms that in-depth and integrated civics education in the campus curriculum can encourage the birth of more aware, proactive, and critical thinking citizens. Practical implications include the importance of strengthening contextual civics education modules and learning based on case studies, interactive, and relevant to current issues among students (Gen Z).